Using Stimulus-Organism-Response Model To Synthesize Dynamics Of Online Impulsive Buying: A Systematic Literature Review - Dr. Rana Muhammad Shahid Yaqub (Corresponding Author) , Dr. Atteeq ur Rehman , Dr. Waqas Manzoor , Sarmina Rustam , Dr. Adnan Bashir (Migration Letters, 2024)
Scholars from many fields are paying more and more attention to online impulsive purchases. However, much work hasn’t been done to assess the state of the field and compile the results into a single body of literature. To fill this study gap, we systematically reviewed the literature on online impulse buying and classified the variables influencing online impulse buying using the Stimulus–Organism–Response (SOR) paradigm. We then build a conceptual framework and Prisma to explain the relationship between the elements that impact online impulse buying. Finally, we discussed future research directions and practical and theoretical implications for research. This review intends to illuminate the multifaceted nature of online impulsive buying through a systematic examination of the available literature. It offers valuable insights that can inform future research agendas and assist businesses and policymakers in developing more effective strategies to manage and harness this consumer behavior phenomenon.